Historical sources of legal protection of nature in Belarus - Balashenko, Siarhei A. (Journal of the Belarusian State University. Law, 2024)
The author of the article examines the historical and legal aspects of the development of legal protection of environment in the Middle Ages, the peculiarities of legal regulation, sanctions, and the evolution of legislative norms in the Grand Duchy of Lithuania with the lands of Belarus as a political centre. The legal regulation of specially protected territories in the three statutes of the Grand Duchy of Lithuania is analysed. The article is dedicated to the researcher of the history of law professor T. I. Dovnar.
Keywords: history of the state and law of Belarus; property right; environmental protection; hunting; forests; specially protected territories; reserve; statutes of the Grand Duchy of Lithuania